2022
DOI: 10.1108/apjba-10-2021-0504
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 catastrophes and stock market liquidity: evidence from technology industry of four biggest ASEAN capital market

Abstract: PurposeThis study examines the influence of various COVID-19 catastrophes variables on the stock market liquidity, considering the market depth and market tightness in the technology industry of the four biggest ASEAN capital markets.Design/methodology/approachThe study utilised the panel data regression analysis obtained from 177 listed technology companies across the four ASEAN countries from March 2, 2020 to June 30, 2021 using the random effect and weighted least squares. The study also supported the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 61 publications
1
4
0
Order By: Relevance
“…This result opposes the research by Alaoui Mdaghri et al [4] which stated that stringency index hampered stock market liquidity significantly. Nevertheless, this result is in line with Nguyen et al's [7] and Priscilla et al's [21] paper. While the theory of black swan stated that the occurrence of a "black swan" might jeopardize investments, this research showed that not all aspects of investments will be hampered.…”
Section: The Effects Of Stringency Index Towards Stock Market Liquiditysupporting
confidence: 89%
“…This result opposes the research by Alaoui Mdaghri et al [4] which stated that stringency index hampered stock market liquidity significantly. Nevertheless, this result is in line with Nguyen et al's [7] and Priscilla et al's [21] paper. While the theory of black swan stated that the occurrence of a "black swan" might jeopardize investments, this research showed that not all aspects of investments will be hampered.…”
Section: The Effects Of Stringency Index Towards Stock Market Liquiditysupporting
confidence: 89%
“…They observed negative impact of coronavirus on stock prices and behavior of investors while governments' financial support played a positive role in reducing the negative impact of the same. Priscilla et al (2022) noticed adverse impact of confirmed cases and deaths on the stock market liquidity; on the contrary, vaccinations and recovery news had positive impact in four ASEAN capital markets. Yarovaya et al (2022) observed a contagion effect and intraregional and interregional return and volatility spillovers based on four levels of information transmission such as catalyst of contagion, media attention, spillover effect at financial markets and macroeconomic fundamentals.…”
Section: Stock Market Volatility and Uncertaintymentioning
confidence: 94%
“…They observed negative impact of coronavirus on stock prices and behavior of investors while governments’ financial support played a positive role in reducing the negative impact of the same. Priscilla et al. (2022) noticed adverse impact of confirmed cases and deaths on the stock market liquidity; on the contrary, vaccinations and recovery news had positive impact in four ASEAN capital markets.…”
Section: Literature Reviewmentioning
confidence: 94%
“…However, Chakrabarty and Pascual (2022) observe a drop in liquidity in assets belonging to the S&P500, although less pronounced in those assets more actively traded by AT. Other papers pointing in this direction are those of Damien (2021), Tissaoui et al (2021), andPriscilla et al (2022). On the other hand, authors such as Marozva and Magwedere (2021) have observed an improvement in liquidity in the capital market, with a negative relationship between illiquidity measures and COVID-19, more prevalent in developed markets than in emerging ones.…”
Section: Literature Reviewmentioning
confidence: 96%